Development of quality index method for anchovy (Engraulis anchoita) stored in ice assessment of its shelf-life by chemical and sensory methods - Massa, A E (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2012)
The objective of this study was to develop a quality index method for Engraulis anchoita stored in ice and to determine its shelf-life based on this quality index method and chemical indices such as total volatile bases and thiobarbituric acid-reactive substances. Besides, the chemical composition with emphasis on the polyunsaturated fatty acids content was determined. The results indicate that E. anchoita is a valuable protein source and lipid with important content of n-3 polyunsaturated fatty acids. The developed quality index method scheme was composed of 28 demerit points, divided into 4 parameters and 10 attributes. All attributes showed correlation with time of storage (R > 0.90). The quality index (QI) presented a linear relationship with storage (QI = 2.55x days in ice + 1.76; R²= 0.98). In the shelf-life assessment-based quality index method, the rejection sensory point was observed after 7 days of storage due to the presence of unpleasant odours and deteriorated appearance. The total volatile basic nitrogen value remained below the upper limit of acceptability during the 10 days of ice storage. The evolution of thiobarbituric acid-reactive substances indicates lipids oxidation during the storage of anchovies. According to the results, the quality index method scheme developed for the E. anchoita stored in ice could be considered adequate to evaluate their freshness and to estimate its shelf-life